Development of Green Fluorescent Protein-Tagged Strains of Fusarium acuminatum via PEG-Mediated Genetic Transformation - Fangyi Ju; Zhongqiang Qi; Jiajin Tan; Tingting Dai (Microorganisms)
Fusarium acuminatum is recognized as the causative agent of root rot in many forestry and agricultural plants. In recent years, root rot and foliage blight caused by F. acuminatum have become widespread and severe in China, particularly affecting Dianthus chinensis. The infection mechanism of F. acuminatum remains a pressing area for research. A crucial approach to elucidating its pathogenic mechanisms involves the genetic modification of candidate genes, which necessitates effective transformation systems. Currently, protoplast-mediated transformation (PMT) serves as a valuable tool for studying plant-pathogen interactions and offers several advantages over conventional transformation methods. In this study, we employed the PMT technique to establish a transformation system for the F. acuminatum strain FDCY-5 due to its benefits such as ease of operation, low cost, high conversion efficiency, and broad applicability. We successfully developed a transformation system capable of producing abundant high-quality protoplasts from F. acuminatum and generating green fluorescent protein (GFP) transformants. To verify whether GFP was constitutively expressed, we utilized fluorescence microscopy alongside PCR technology. The results demonstrated that GFP was effectively transformed into the protoplasts of F. acuminatum and expressed successfully. The established protoplast transformation system for F. acuminatum provides a foundational platform for analyzing functional genes within infected host plants as well as understanding the molecular mechanisms underlying host plant infections by F. acuminatum.